Optimal design of deep stormwater drainage tunnels to address urban flooding in Korea - Cho, Yong Jun (Scientific reports, 2024)
Deep stormwater drainage tunnels play a crucial role in mitigating severe urban flooding in Korea, particularly as climate change leads to more extreme weather events. These tunnels typically consist of an entrance reservoir, a circular reinforced concrete culvert with a flat slope, a downstream reservoir, and an outlet to a nearby river. In this system, the flow within the circular culvert is driven solely by the momentum of free-falling stormwater runoff. However, concerns have emerged within the Korean water resources engineering community about the drainage capacity of these tunnels, even with a substantial fall height of approximately 30 m. Intensified localized rainfall, the abrupt transition from flood waves to pressurized flow within the circular culvert, and trapped air pockets can also pose significant challenges to the tunnel’s drainage efficiency. Conventional design methods often fail to optimize the culvert’s diameter and spatial configuration, leading to suboptimal performance. In response, this study utilizes 3D numerical simulations with the interFoam solver from the OpenFOAM toolbox to address these issues. The results indicate that smaller culvert diameters—provided they do not exceed the maximum permissible flow velocity—enhance drainage capacity by reducing the impact of shock waves and stabilizing flow. These findings challenge the prevailing design practice in Korea, which holds that larger culverts inherently offer superior drainage capacity. Moreover, the simulations suggest that as culvert diameters increase, the size of trapped air pockets grows, further reducing efficiency. Although air chambers can help mitigate the retarding effects of trapped air pockets, their effectiveness diminishes if positioned near the origin of shock waves, where they risk being filled with stormwater. Based on these insights, several key recommendations are proposed: First, the design of deep stormwater tunnels should prioritize minimizing the extent of trapped air pockets, even when air chambers are used. Second, the current focus on detention capacity in design practices should be reevaluated, as excessive detention capacity may exacerbate air pocket formation. Finally, modifying the inlet channel to induce spiral flow within the entrance reservoir could reduce impulsive forces, lower maintenance costs related to armoring rocks at the reservoir bottom, and stabilize flow more quickly, thereby enhancing overall drainage capacity.